Evaluation of formocresol versus mineral trioxide aggregate in primary molar pulpotomy: Meta-analysis [Procjena djelovanja formokrezola u odnosu na agregat mineralnogtrioksida kod mliječnih kutnjaka liječenih pulpotomijom: Meta-analiza] - (:unkn) unknown (My University, 2010)
Aim: The aim of this study is to present a systematic review of the effects of formocresol (FC) and mineral trioxide aggregate (MTA)when used as medicaments in pulpotomized primary teeth. Methods: Methodology of the study list was obtained by using MEDLINE, PubMed, SCI and Marmara University Library. Totally 165 studies were performed. Studies of interest were randomized controlled trials of primary molar teeth where there was exposure of vital pulp caused by caries or trauma, treated by using MTA or FC pulpotomy, with at least 6 months follow-up, and radiographic evidence. Meta - analysis was performed using Comprehensive Meta-Analysis, Version 2.0(2005). Fixed effect model was applied to aggregate data. Results: Six studies that include criteria were used. Totally 195 teeth treated by MTA and 203 teeth treated by FC. The radiographic success for treatment with MTA or FC in the 6 studies ranged from 72% to 100%. Data were extracted from each study independently and entered into a database. Differences were resolved by discussion. The general odds-ratio was found 1.146. There was a homogeneity among the studies (Q-value= 9.865, df=5, p=0.079). Conclusions: Evidence based dentistry is being used increasingly as a tool to synthesize, evaluate, and interpret research to produce clinical guidelines and conclusions. The results demonstrate that in primary molar teeth with vital pulp exposure caused by caries or trauma, a pulpotomy performed with MTA results is not better than FC radiographically observed outcomes.
Keywords: Dentition; Formocresol; Meta-analysis; Mineral trioxide aggregate; Primary; Pulpotomy